THE INFLUENCE OF MARKETING MIX ON PATIENT SATISFACTION IN THE INPATIENT WARD OF GRAHA HUSADA HOSPITAL IN 2025 - Fitri, Azza Nur Laila; Sunita, Anna; Rinaldi, Enrico Adhitya (UTSAHA: Journal of Entrepreneurship, 2025)
Intensifying competition within the healthcare service sector necessitates that hospitals adopt effective strategies to sustain and enhance patient satisfaction levels. The implementation of marketing mix principles represents one such strategic approach. This investigation was conducted at Graha Husada Hospital Tuban, a type D referral facility situated in the southern region of Tuban Regency. The research employed an extended 4P marketing mix framework encompassing product, price, place, and promotion, supplemented by physical evidence as a critical component representing patients' perceived service quality among inpatients. The primary objective of this study was to examine the influence of marketing mix elements (product, price, place, promotion, and physical evidence) on patient satisfaction and to assess the effectiveness of marketing mix educational interventions. This quantitative investigation utilized a pre-experimental one-group pretest-posttest design. Fifty inpatients were recruited through purposive sampling methodology. The intervention comprised educational brochure distribution, with measurements conducted pre- and post-intervention using validated structured questionnaires. Statistical analyses were performed using paired t-tests and Pearson correlation coefficients. Results demonstrated a significant increase in patient satisfaction following the intervention, with mean scores increasing from 89.14 to 100.62. Pearson correlation analysis revealed that physical evidence (r = 0.732) and product quality (r = 0.719) exhibited the strongest associations with patient satisfaction, whereas price demonstrated no statistically significant influence. Overall, the marketing mix demonstrated a significant positive correlation with patient satisfaction (r = 0.699; p < 0.05). The educational intervention focusing on marketing mix principles effectively enhanced inpatient satisfaction at Graha Husada Hospital Tuban.